Speaker and Speech Recognition Using Hierarchy Support Vector Machine and Backpropagation - Asti F. Fadlilah; Esmeralda C. Djamal (IAES Indonesia Section, 2019)
Voice signal processing has been proposed to improve effectiveness and facilitate the public, such as Smart Home. This study aims a smart home simulation model to move doors, TVs, and lights from voice instructions. Sound signals are processed using Mel-frequency Cepstrum Coefficients (MFCC) to perform feature extraction. Then, the voice is recognized by the speaker using a hierarchy Support Vector Machine (SVM). So that unregistered speakers are not processed or are declared not having access rights. For the process of recognizing spoken words such as